Remains of the German outlaw Johannes Bückler alias Schinderhannes identified by an interdisciplinary approach - Parson, Walther; Alterauge, Amelie; Amory, Christina; Heinze, Sarah; Hölzl, Stefan; Jahn, Ralf G.; Lehn, Christine; Sänger, Timo; Xavier, Catarina; Tillmar, Andreas; Nolte, Karen; Lutz-Bonengel, Sabine; et al. (Forensic science international. Genetics, 2025)
Two mounted skeletons assigned to the famous German criminals Schinderhannes and Hölzerlips were on display at the Anatomical Collection of Heidelberg University for two centuries. However, doubts about their authenticity existed for decades. Based on historical research, an interdisciplinary team with experts from the fields of anatomy, radiology, anthropology, genealogy and molecular biology set out to examine the remains from the following perspectives: (1) Isotope analyses were carried out to compare inferred childhood residences with historical narratives, (2) anthropological and radiological examinations were documented and compared with historical records, (3) genealogical research identified a living male descendant along the maternal line and (4) mitogenome sequencing as well as nuclear SNP analysis using the FORCE panel provided compelling evidence for the identification of Schinderhannes’ remains. Additionally, the prediction of eye, hair and skin color from the DNA offered science-based data to clarify conflicting historical records.